The Strategies of Rebulding Iraqi Cities That War Destroyed (Journal of the College of Education for Women, 2019)
This study includes the rebuilding of cities that war destroyed, which include some of the special policies that should be followed in order to build cities that war destroyed and which have importance in the national and humanitarian level, as well as some international experiences discussed including Warsaw, and the regional experiences, including Lebanon and concentrates on the foundation stone and evaluate it with global and regional experiences so that we can concluded with an integrated strategy that will achieve the best results in doing the reality that we live in these cities which are suffering from such disasters . In order to achieve the best goals we should review the best concepts and theories related to reconstruction after the war, this study summed up a set of conclusions and recommendations which represented the building theories, which represents ground for rebuilding strategy for reconstruction and this result to show some global and regional experiences and compare them with reality to avoid the mistakes that soak thus to draw a successful policy and strategy which can be guided us to build those cities in a sustainable manner and lower costs .